Advection, Surface Area, and Sediment Load of the Fraser River Plume Under Variable Wind and River Forcing. Issue 4 (20th October 2017) - Pawlowicz, R.; Di Costanzo, R.; Halverson, M.; Devred, E.; Johannessen, S.
ABSTRACT: The Fraser River is the source of most particulate matter in the Strait of Georgia, and its dispersal is modulated by the Fraser's plume. Here we examine the plume's shape, location, and area, and the variation of these parameters with changes in wind and river forcing by examining a 13-year time series of Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery for the concentration of suspended particulate matter (SPM). Plume shape and its variations are quantified by dividing the 904 images in this time series into subsets showing conditions under specified wind and river flow conditions and forming a composite image for each subset. Quantitative analysis of scalar quantities like plume area and mean plume SPM are based on calculated values for all individual images. The plume area increases linearly with river flow, changing by a factor of 10 between lowest and highest flows. Mean plume SPM also changes with flow but only by a factor of two. The surface area of the plume is almost completely unaffected by wind conditions. Plume location, however, is very sensitive to both wind speed and direction. It can reach across the Strait at highest river flows and is advected either northwest or southeast along the Strait in the same direction as winds on daily time scales. We also estimate the residence time of sediment in the plume to be only a few days, allowing the plume itself to reshape rapidly over short time scales in response to weather conditions.